Potential dangers of Deoxynivalenol; A review - Afandi, Ryan; Ekowati, Juni; Rudyanto, marcellino (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2025)
Background: Deoxynivalenol (DON) is a type of mycotoxin produced by Fusarium fungi particularly Fusarium graminearum. This mycotoxin is commonly found in various crops, including wheat, maize, and barley. DON is one of the most commonly found mycotoxins in crops and can cause significant economic losses in the agriculture and livestock industries. Therefore, monitoring and controlling DON levels is crucial to ensure food safety and animal health. Method: study literature review method by collecting various journals that investigate Fusarium graminearum contamination and the associated risks of deoxynivalenol Results: Effects on human health cause gastrointestinal disturbances, damage to the digestive tract, and toxic effects on the immune system, while on animals cause been shown to reduce the production of milk, eggs, and meat. Conclusion: DON is a common mycotoxin found in agricultural products, posing a threat to human and animal health. Therefore, a rapid and effective detection method is needed to overcome DON contamination.